Oncostatin M, Serpins, and Oxidative Stress in Extracellular Matrix Remodeling and Arteriovenous Fistula Maturation - DeMarco, Nathaniel; Rai, Vikrant; Wilson, Daniel R; Agrawal, Devendra K (Cardiology and Cardiovascular Medicine, 2023)
End-stage renal disease is a crippling diagnosis that generally requires dialysis to prolong life. To facilitate filtration of patient’s blood in dialysis, surgical formation of an arteriovenous fistula (AVF) is commonly performed. Maturation of the AVF is required to allow for successful dialysis. However, AVFs commonly fail to mature, leading to the fistula closure, the necessity for another fistula site, and markedly increased morbidity and mortality. The current literature concerning molecular mechanisms associated with AVF maturation failure supports the role of inflammatory mediators involving immune cells and inflammatory cytokines. However, the role of oncostatin M (OSM), an inflammatory cytokine, and its downstream targets are not well investigated. Through inflammation, oxidative stress, and hypoxic conditions, the vascular tissue surrounding the AVF undergoes fibrosis, stenosis, and wall thickening, leading to complete occlusion and nonfunctional. In this report, first we critically review the existing literature on the role of OSM in the most common causes of early AVF failure - vascular inflammation, thrombosis, and stenosis. We next consider the potential of using OSM as a therapeutic target, and finally discuss therapeutic agents targeting inflammatory mediators involved in OSM signaling to potentiate successful maturation of the AVF.